Charming as a verb - Philippe, Ben (Balzer + Bray, an imprint of HarperCollins Publishers, 2020)
Henri "Halti" Haltiwanger can charm just about anyone. But his easy smiles mask a burning ambition to attend his dream college, Columbia University. There is only one person who seems immune to Henri's charms: his "intense" classmate and neighbor Corinne Troy. When she uncovers Henri's less-than-honest dog-walking scheme, she blackmails him into helping her change her image at school. Henri agrees, seeing a potential upside for himself. Soon what started as a mutual hustle turns into something more surprising than either of them ever bargained for ... --